An active fault tolerant control approach to an offshore wind turbine model. (March 2015) - Shi, Fengming; Patton, Ron
Abstract: The paper proposes an observer based active fault tolerant control (AFTC) approach to a non-linear large rotor wind turbine benchmark model. A sensor fault hiding and actuator fault compensation strategy is adopted in the design. The adapted observer based AFTC system retains the well-accepted industrial controller as the baseline controller, while an extended state observer (ESO) is designed to provide estimates of system states and fault signals within a linear parameter varying (LPV) descriptor system context using linear matrix inequality (LMI). In the design, pole-placement is used as a time-domain performance specification while H ∞ optimization is used to improve the closed-loop system robustness to exogenous disturbances or modelling uncertainty. Simulation results show that the proposed scheme can easily be viewed as an extension of currently used control technology, with the AFTC proving clear "added value" as a fault tolerant system, to enhance the sustainability of the wind turbine in the offshore environment. Highlights: The chief aim is to develop a new design strategy for wind turbines to enhance sustainability of system operation. The design approach is focused on a strategy that takes into account parametric variations in the wind turbine dynamics. The use of a linear parameter-varying (LPV) descriptor systems framework for modeling, control and estimation. Bounded fault effects are estimated robustly on-line and compensated for within the control systems. The existing control system can be retained and the fault tolerant control system involves an additional "bolt on" scheme.